Weight loss as a predictor of poor prognosis in patients hospitalized for COVID-19 - Paiva, Brena Letícia Gomes de (2023)
Objective: To evaluate the relationship between weight loss and markers of poor prognosis in patients hospitalized with COVID-19 in the state of Pernambuco. Methods: A multicenter, cross-sectional study coupled with prospective analysis variables involving 71 individuals with COVID-19 admitted for hospitalization in 8 public hospitals in Recife, in the State of Pernambuco. Individuals of both sexes, aged ≥ 20 years, hospitalized from June 2020 to June 2021 were included. Sociodemographic, clinical, and nutritional data and prognostic markers were collected. Results: The average age was 54.6±15.6 years, with 54.9% of individuals being male. It was found that 26.8% of the patients were diabetic and 52.1% were hypertensive. The anthropometric profile indicated that 56.3% were overweight and 5.6% were underweight. Positive screening for sarcopenia was observed in 16.9%. The median weight loss was 3.1% (0.0-6.6%), with a loss > 5% evident in 29.6% of the sample. It was found that weight loss was more frequent in men (16 (41.0%) vs. 5 (15.6%); p = 0.020) and that demographic, clinical, and nutritional variables were not associated with body weight loss. There was no statistical association between weight loss and prognostic variables (p NS). Conclusion: Although the study did not demonstrate an association between weight loss and prognostic variables, this should be considered when assessing patients with COVID-19 and should be investigated and treated as an essential health promotion measure.